0642 The Effect of Bright Light on Temperature, Sleepiness, and Salivary Melatonin in Shift Work Nurses. (12th April 2019) - Maghsoudipour, Maryam; Hosseinzadeh, Samaneh; Parkhoo, Mohammad; Ansari, Mohammad; Karbasi, Ashkan
Abstract: Introduction: To assess the effect of bright light emitted by a light-box in nurse station, on sleepiness, oral temperature, and salivary melatonin in night-shift nurses. Methods: In a prospective, interventional, crossover trial 44 healthy female night-shift nurses were allocated into two groups of intervention and control. In the first stage, the nurses in the intervention group were exposed to 10000 lux bright light by a light-box at 11 p.m. for half an hour. The control group were not exposed to bright light. In the next stage (one month later), the control group of the first stage was exposed to bright light as the intervention group of the second stage and vice versa. Karolinska Sleepiness Scale (KSS) and oral temperature were assessed every hour during next 24 hours. Salivary melatonin was measured at 4 a.m. during shift day and 4 p.m. after shift. A linear mixed model was used for analysis. Results: Bright light exposure had significant influence on temperature and KSS over the 24 hours period time(P-value < 0.001 for all). The mean of temperature and KSS in two groups of cases and controls in both periods were significantly different. The trend of changes of temperature and KSS in two groups had opposite directions. The trend of changes in melatonin concentrations was different between case and control group. In the intervention group the mean values were increasing, and in the control group were decreasing (P-value < 0.001). While Bright light exposure resulted in occurrence of the minimum KSS at 4 a.m., and the maximum KSS at 4 p.m., it resulted in decreased concentrations of melatonin in the early morning (compared to the next evening), and maximum temperature at 4 a.m. compared to minimum temperature at 2 p.m.. Conclusion: Bright light exposure at 11 p.m. changes the pattern of sleepiness, oral temperature, and salivary melatonin in night-shift nurses. These effects will help the nurses to better tolerate the shift hours and have better sleep at home. Support (If Any): Not